Evidence-based Examination of the Consequences of Financial Development on Environmental Degradation in the Indian Setting, Using the ARDL Model - Esquivias, Miguel Angel; Hassan, Owais ibni; Sheikh, Aisha (International Journal of Energy Economics and Policy, 2023)
The purpose of this study is to investigate India's long-run equilibrium relationship between carbon emissions, financial development, energy consumption, urbanization and trade openness from 1960 to 2020. The analysis of the sources of carbon emissions by taking into account the role that financial growth and trade openness plays and using data from a single country is the most significant contribution that we have made to the existing body of research on Indian studies, using an updated dataset and methodology. According to the findings, there is evidence of long-term relationship between trade openness, financial development, urbanization, energy consumption and carbon emissions. Given that each of the variables has a positive association with the carbon emissions; this indicates that each of the variables contributes to environmental degradation, since they emit a significant amount of CO2 into the atmosphere, in the context of India over the time period of the study that was observed. According to the data presented, the functioning of the financial system ought to incorporate an awareness of its impact on the surrounding environment. The findings of this study could be of tremendous significance for those responsible for formulating policies and making decisions in the area of energy in India, particularly those that contribute to the reduction of carbon emissions while maintaining environmental integrity